Analysis of Finnish chemistry Matriculation Examination questions according to Cognitive Complexity - Greta Tikkanen; Maija Aksela (Nordina: Nordic Studies in Science Education, 2012)
This paper presents an analysis of Finnish chemistry matriculation examination questions according to cognitive complexity. The research data consisted of 257 questions from 28 matriculation examinations between 1996 and 2009. Qualitative approach and theory-driven content analysis method using Bloom’s revised Taxonomy of Cognitive Objectives were employed in the research. The categories of the higher-order (HOCS) and lower-order cognitive skills (LOCS) were formed on the basis of earlier research. This research was guided by the following question: What kinds of cognitive skills and knowledge do Finnish chemistry matriculation examination questions require? The research indicates that the examinations were cognitively demanding. The majority (77%) of the questions required higher-order cognitive skills. The Bloom’s revised Taxonomy of Cognitive Objectives as used in this research gives a useful way for designing or analysing chemistry summative assessment tools. All three higher-order cognitive skills (HOCS) categories should be more evenly presented in chemistry matriculation examinations.